ER stress induced immunopathology involving complement in CADASIL: implications for therapeutics - Mahmod Panahi; Yoshiki Hase; Xavier Gallart-Palau; Sumonto Mitra; Atsushi Watanabe; Roger C Low; Yumi Yamamoto; Diego Sepulveda-Falla; Atticus H Hainsworth; Masafumi Ihara; Siu Kwan Sze; Matti Viitanen; et al. (Acta Neuropathologica Communications, 2023)
Abstract Cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is caused by NOTCH3 mutations. Typical CADASIL is characterised by subcortical ischemic strokes due to severe arteriopathy and fibrotic thickening of small arteries. Arteriolar vascular smooth muscle cells (VSMCs) are the key target in CADASIL, but the potential mechanisms involved in their degeneration are still unclear. Focusing on cerebral microvessels in the frontal and anterior temporal lobes and the basal ganglia, we used advanced proteomic and immunohistochemical methods to explore the extent of inflammatory and immune responses in CADASIL subjects compared to similar age normal and other disease controls. There was variable loss of VSMC in medial layers of arteries in white matter as well as the cortex, that could not be distinguished whether NOTCH3 mutations were in the epidermal growth factor (EGFr) domains 1–6 or EGFr7-34. Proteomics of isolated cerebral microvessels showed alterations in several proteins, many associated with endoplasmic reticulum (ER) stress including heat shock proteins. Cerebral vessels with sparsely populated VSMCs also attracted robust accrual of perivascular microglia/macrophages in order CD45+ > CD163+ > CD68+cells, with > 60% of vessel walls exhibiting intercellular adhesion molecule-1 (ICAM-1) immunoreactivity. Functional VSMC cultures bearing the NOTCH3 Arg133Cys mutation showed increased gene expression of the pro-inflammatory cytokine interleukin 6 and ICAM-1 by 16- and 50-fold, respectively. We further found evidence for activation of the alternative pathway of complement. Immunolocalisation of complement Factor B, C3d and C5-9 terminal complex but not C1q was apparent in ~ 70% of cerebral vessels. Increased complement expression was corroborated in > 70% of cultured VSMCs bearing the Arg133Cys mutation independent of N3ECD immunoreactivity. Our observations suggest that ER stress and other cellular features associated with arteriolar VSMC damage instigate robust localized inflammatory and immune responses in CADASIL. Our study has important implications for immunomodulation approaches to counter the characteristic arteriopathy of CADASIL.